Solving SIP by penalty techniques: merit functions and filter method - Pereira, Ana I. (2011)
We present a review of reduction type methods to solve nonlinear semi-infinite programming problems. In the last years a large type of techniques were presented in literature to solve SIP problems based on reduction method. These reduction type methods presented are based on merit functions and filter method combined with penalty techniques. Some comparations are made.